Best Answer

To:

trantancuong21@Yahoo.com

Le dernier théorème de Pierre de Fermat .

(x, y, z, n) l'ensemble de ( N+ )^4.

n> 2.

( a ) l'ensemble de Z

F est la fonction de (a).

F (a) = [a (a +1) / 2] ^ 2

F (0) = 0 et F (-1) = 0.

Considérons deux équations.

F (z) = F (x) + F (y)

F (z-1) = F (x-1) + F (y-1)

Nous avons une inférence chaîne

F (z) = F (x) + F (y) équivalent F (z-1) = F (x-1) + F (y-1)

F (z) = F (x) + F (y) en déduire F (z-1) = F (x-1) + F (y-1)

F (z-x-1) = F (x-x-1) + F (y-x-1) en déduire F (z-x-2) = F (x-x-2) + F (y-x-2)

nous voyons

F (z-x-1) = F (x-x-1) + F (y-x-1)

F (z-x-1) = F (-1) + F (y-x-1)

F (z-x-1) = 0 + F (y-x-1)

donner

z = y

et

F (z-x-2) = F (x-x-2) + F (y-x-2)

F (z-x-2) = F (-2) + F (y-x-2)

F (z-x-2) = 1 + F (y-x-2)

donner z = / = y.

de sorte

F (z-x-1) = F (x-x-1) + F (y-x-1) ne pas en déduire F (z-x-2) = F (x-x-2) + F (y-x-2)

de sorte

F (z) = F (x) + F (y) ne pas en déduire F (z-1) = F (x-1) + F (y-1)

de sorte

F (z) = F (x) + F (y) n'est pas équivalente F (z-1) = F (x-1) + F (y-1)

Donc avoir deux cas.

[F (x) + F (y)] = F (z) et F (x-1) + F (y-1)] = / = F (z-1)

ou vice versa

de sorte

[F (x) + F (y)] - [F (x-1) + F (y-1)] = / = F (z)-F (z-1).

Ou

F (x)-F (x-1) + F (y)-F (y-1) = / = F (z)-F (z-1).

nous voyons

F(x)-F(x-1) =[x(x+1)/2]^2 - [(x-1)x/2]^2.

=(x^4+2x^3+x^2/4) - (x^4-2x^3+x^2/4).

=x^3.

F(y)-F(y-1) =y^3.

F(z)-F(z-1) =z^3.

de sorte

x 3 + y ^3 =/= z ^ 3.

n> 2. . Similaire.

Nous avons une inférence chaîne

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) équivalente G (z) * F (z-1) = G (x) * F (x -1) + G (y) * F (y-1)

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) en déduire G (z) * F (z-1) = G (x) * F (x -1) + G (y) * F (y-1)

G (z) * F (z-x-1) = G (x) * F (x-x-1) + G (y-x-1) * F (y) en déduire G (z) * F (z-x-2) = G ( x) * F (x-x-2) + G (y) * F (y-x-2)

nous voyons

G (z) * F (z-x-1) = G (x) * F (x-x-1) + G (y) * F (y-x-1)

G (z) * F (z-x-1) = G (x) * F (-1) + G (y) * F (y-x-1)

G (z) * F (z-x-1) = 0 + G (y) * F (y-x-1)

donner z = y.

et

G (z) * F (z-x-2) = G (x) * F (x-x-2) + G (y) * F (y-x-2)

G (z) * F (z-x-2) = G (x) * F (-2) + G (y) * F (y-x-2)

G (z) * F (z-x-2) = G (x) + G (y) * F (y-x-2)

x> 0 en déduire G (x)> 0.

donner z = / = y.

de sorte

G (z) * F (zx-1) = G (x) * F (xx-1) + G (yx-1) * F (y) ne pas en déduire G (z) * F (z-x-2) = G (x) * F (x-x-2) + G (y) * F (y-x-2)

de sorte

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) ne pas en déduire G (z) * F (z-1) = G (x) * F (x-1) + G (y) * F (y-1)

de sorte

G (z) * F (z) = G (x) * F (x) + G (y) * F (y) n'est pas équivalente G (z) * F (z-1) = G (x) * F (x-1) + G (y) * F (y-1)

Donc avoir deux cas

[G (x) * F (x) + G (y) * F (y)] = G (z) * F (z) et [G (x) * F (x-1) + G (y) * F (y-1)] = / = G (z-1) * F (z-1)

ou vice versa.

de sorte

[G (x) * F (x) + G (y) * F (y)] - [G (x) * F (x-1) + G (y) * F (y-1)] = / = G (z) * [F (z)-F (z-1)].

Ou

G (x) * [F (x) - F (x-1)] + G (y) * [F (y)-F (y-1)] = / = G (z) * [F (z) -F (z-1).]

nous voyons

x ^ n = G (x) * [F (x)-F (x-1)]

y ^ n = G (y) * [F (y)-F (y-1)]

z ^ n = G (z) * [F (z)-F (z-1)]

de sorte

x ^ n + y ^ n = / = z ^ n

Le bonheur et la paix

Tran Tan Cuong

Q: Who is person who solve shortest Fermat?

Write your answer...

Submit

Still have questions?

Related questions

Andrew Wiles

Fermat's Last Theorem

long time.

Pierre de Fermat. The problem was called Fermat's Last Theorem

Fermat Prize was created in 1989.

Out of all possible paths that light might take, to get from one point to another, it takes the path that requires the shortest time.

Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.Yes, the famous Fermat's Last Theorem, a conjecture by Fermat, that an equation of the form an + bn = cn has no integer solution, for n > 2. This was conjectured by Fermat in 1637, but it was only proved in 1995.

who meny juseph have fermat

Out of all possible paths that light might take, to get from one point to another, it takes the path that requires the shortest time.

Fermat's Room was created on 2007-10-07.

It was 1647 not 1847 and by Fermat himself.

Shirley Temple was the shortest person to win an oscar.